Management of Extramammary Paget's Disease: A Case Report and Review of the Literature - Rosa Guerra; Subhasis Misra (Case Reports in Dermatological Medicine)
Extramammary Paget's Disease (EMPD) is a rare condition of the skin that often involves the vulva, perianal region, scrotum, penis, and axilla. Although prognosis is generally favorable, it can be associated with neoplasms of the bladder, urethra, prostate, and rectum. This report presents a case of scrotal EMPD that failed treatment with imiquimod 5% cream and discusses benefits and complications of available treatment options. The variation of treatment success emphasizes the importance of further research.